IMPROVING THE REGULATION AND INCENTIVE FEATURES OF PERSONAL INCOME TAXATION - Ruziev Ghanisher Usarovich (American Journals, 2025)
This article provides relevant proposals and recommendations for further improving the regulation and incentive mechanisms of personal income taxation in Uzbekistan, based on a study of international experience in taxing individual incomes.
Keywords: Income tax, social justice, standard of living, minimum consumption expenditure, progressive scale, non-taxable minimum.